INVESTIGATION OF THE THERMAL PERFORMANCE OF A SOLAR ASSISTED AIR CONDITIONER UNDER TROPICAL CLIMATE - NESARAJ, JESHURUN (IRC, 2017)
Air conditioning is a process that includes heating, cooling, humidification, dehumidification, cleaning and circulation of air in an enclosed space. Air conditioners are the main equipment’s in a Heating, Ventilation and air conditioning (HVAC) system. In a tropical weather country like Malaysia, the demand for cooling of indoor air is growing due to increasing comfort expectations and cooling loads. Air conditioning have now become a necessity for providing indoor cooling in majority of buildings in Malaysia. These buildings use conventional cooling technologies which commonly uses lots of energy. Due to this, renewable energy sources have become a solution to help overcome this problem. Solar air-conditioning is one of the ways to reduce the demand for electricity. Conventional air conditioners consist of a compressor, a condenser, an expansion valve and an evaporator. Similar to this is also a solar air conditioner except for its additional part which is the solar collector. This solar collector acts as a heat absorber for the refrigerant passing through it. A conventional air conditioner consumes electricity but a solar air conditioner consumes partial electricity and partial solar energy. Therefore, the load on this solar air conditioner will be less than the conventional one. For this process, refrigerant 407 C is used because of its positive impact towards the environment. To assess the performance of these two types of air conditioners, the working principle and the difference in the refrigeration cycle is analysed. In order to measure the pressure and temperature of the refrigerant as well as the humidity, a software called iManifold is used to measure required parameters and sends the observation straight to a smart phone using the installed application. Specific iManifold probes are used to obtain readings from the air conditioner. This performance can then be transferred to the generation of P-V or T-S diagram. Based on the difference in power consumption, the mitigation of carbon dioxide gas can be evaluated. As for monitoring and measurement purposes, the difference in cooling performance of this air conditioner is compared to the outside air and taken to consideration.